MLH1/PMS2 Expression Could Tell Classical NTRK Fusion in Fluorescence In Situ Hybridization Positive Colorectal Carcinomas - Fu, Yao; Li, Zheng; Gao, Fuping; Yang, Jun; Wu, Hongyan; Zhang, Biao; Pu, Xiaohong; Fan, Xiangshan (Frontiers in Oncology, 2021)
To gain insight into the clinicopathologic profile of colorectal carcinomas harboring oncogenic NTRK fusions based on eastern populations as well as make the best testing algorithm for the screen, we use pan-Trk immunohistochemistry (IHC), fluorescence in situ hybridization (FISH) respectively to screen NTRK fusions in a large, unselected cohort of 819 colon cancers, either IHC or FISH positive cases were further detected by next-generation sequencing (NGS). IHC staining was observed in ten (1.22%) cases, FISH positive was observed in 13(1.59%) cases, and finally, a total of 18 cases were under both a DNA-based and an RNA-based NGS assay. RNA-based NGS was positive in 13 of 18 cases whereas DNA-based NGS was only positive in three of 18 cases. In total 13 RNA-based NGS NTRKs fusion-positive cases, only six cases were pan-TRK IHC positive versus 12 were FISH positive. More important, in 13 RNA-based NGS cases only five cases containing the full length of NTRK tyrosine kinase (TK) domain and forming the classical fusion chimeras, other six cases only maintaining parts of the TK domain and forming the sub- classical fusion chimeras, two cases totally missing the TK domain and forming the non- classical fusions. For clinicopathologic characteristics, besides MMR (mismatch repair) status (p=0.001), there is no difference between NTRK fusion-positive and negative cases. Nevertheless, classical fusion cases prefer to low differentiation (p=0.001) and different pattern of growth(p˂0.001). Besides, we found all five classical NTRK fusion cases and only one sub-classical case were harboring MLH1/PMS2 deficiency. When combining FISH and MMR(Mismatch Repair) status, besides one sub-classical case, all five classical fusion were all detected, which means MLH1/PMS2 expression could further narrow classical fusions in FISH NTRK fusion positive cases. Given the low sensitivity and specificity of the pan-Trk antibody, it would be useless to use IHC to screen NTRK fusion-positive CRCs. Combine FISH and MLH1/PMS2 IHC would be a good testing algorithm for the screen effective NTRK fusions. Finally, if patients are going to undergo TRK-based targeted therapy only RNA-based NGS for detection of the specific fusion could tell the precise rearrangement information.